The protection of the underwater cultural heritage in the Convention on the Protection of the Underwater Cultural Heritage 2001 - Miranda Gonçalves, Rubén (Derecho Público Iberoamericano, 2016)
This article discusses the development of the rule that filled a legal vacuum on the matter to be analyzed. Throughout this study we will discuss the legal status of the Underwater Cultural Heritage Convention 2001, studying its birth, objectives and the general principles that establishes and the protection of the underwater cultural heritage in various marine areas. Finally, it highlights its entry into force will and ends with the relation of states that have ratified or approved it. The object of analysis is especially relevant since it should be noted that until 2001 there wasn’t international text that would protect this area specifically.